Effect of NaCl stress on exoproteome profiles of Bacillus amyloliquefaciens EB2003A and Lactobacillus helveticus EL2006H - Naamala, Judith; Subramanian, Sowmyalakshmi; Msimbira, Levini A.; Smith, Donald L. (Frontiers in Microbiology, 2023)
Salt stress can affect survival, multiplication and ability of plant growth promoting microorganisms to enhance plant growth. Changes in a microbe's proteome profile is one of the mechanisms employed by PGPM to enhance tolerance of salt stress. This study was focused on understanding changes in the exoproteome profile of Bacillus amyloliquefaciens EB2003A and Lactobacillus helveticus EL2006H when exposed to salt stress. The strains were cultured in 100 mL M13 (B. amyloliquefaciens) and 100 mL De man, Rogosa and Sharpe (MRS) (L. helveticus) media, supplemented with 200 and 0 mM NaCl (control), at pH 7.0. The strains were then incubated for 48 h (late exponential growth phase), at 120 rpm and 30 (B. amyloliquefaciens) and 37 (L. helveticus) ℃. The microbial cultures were then centrifuged and filtered sterilized, to obtain cell free supernatants whose proteome profiles were studied using LC-MS/MS analysis and quantified using scaffold. Results of the study revealed that treatment with 200 mM NaCl negatively affected the quantity of identified proteins in comparison to the control, for both strains. There was upregulation and downregulation of some proteins, even up to 100%, which resulted in identification of proteins significantly unique between the control or 200 mM NaCl (p ≤ 0.05), for both microbial species.Proteins unique to 200 mM NaCl were mostly those involved in cell wall metabolism, substrate transport, oxidative stress tolerance, gene expression and DNA replication and repair. Some of the identified unique proteins have also been reported to enhance plant growth. In conclusion, based on the results of the work described here, PGPM alter their exoproteome profile when exposed to salt stress, potentially upregulating proteins that enhance their tolerance to this stress.